Factors Affecting Intellectual Capital Disclosure in Indonesia Banking Companies with Board Turnover as Moderating Variable - Mochtar, Raja Ade Fitrasari; Yusnita, Raja Ria; Nursida, Nina (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to investigate the relationships between the variables of Proportion of Independent Commissioners, Managerial Ownership, External Auditor Quality, Company Size, and Gender Diversity concerning Intellectual Capital Disclosure, with Board Turnover as a moderating variable. Data sourced from the annual reports of banking companies listed on the Indonesia Stock Exchange spanning from 2018 to 2022 are employed, encompassing 35 out of a total of 47 banking companies. The methodological approach employed is panel data regression analysis, and SmartPLS serves as the analytical tool to assess the hypothesis model. Research findings indicate a positive impact of External Auditor Quality, Company Size, and Gender Diversity on Intellectual Capital Disclosure. Moreover, the empirical evidence suggests no significant influence of the variables Proportion of Independent Commissioners and Managerial Ownership on Intellectual Capital Disclosure. Additionally, Board Turnover, as a moderating variable, is found to be incapable of strengthening the relationships between the Proportion of Independent Commissioners, Managerial Ownership, External Auditor Quality, Company Size, and Gender Diversity in relation to Intellectual Capital Disclosure.